Pelatihan Platform Pembelajaran Edmodo pada Guru-guru SMK PGRI 3 Kediri - Nurhajati, Diani; Kencanawati, Dewi; Wicaksono, Agung; Khoiriyah, Khoiriyah; Badarudin, Luhung; Putri, Maria Gabriela Nawang (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Due to the Covid-19 Pandemic, teachers are required to carry out online learning. They may utilize technology in implementing the learning. They can choose one of interesting and interactive learning media in order to motivate their students and to promote learning. Based on the preliminary study in SMK PGRI 3 Kediri, it was found out that many teachers had not utilized the available learning platform. They only applied the application they were familiar to support their online learning, such as WhatsApp, Google Class, and Google Meet. Realizing the facts, the community service team carried out a training for the teachers to use interactive platform as media for learning, called Edmodo. The objectives the program were to train the teachers to use Edmodo platform for interactive learning, that included how to make new Edmodo accounts, how to make use the available facilities in Edmodo, and to train the school administrator to manage the program. The training was carried out in one month using in-and-on basis. The results of the training were that all teachers have already had Edmodo accounts and their account are connected with Edmodo group, which could be monitored by the school administrator.